PANDANGAN HUKUM ISLAM TERHADAP PEMBAGIAN WARISAN SEBELUM MUWARIS MENINGGAL DI DUSUN PENGKOLAN - Oktavi Cindyani; WANDA RAMADHANI (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Inheritance according to Islamic law is the process of transferring the inheritance of someone who has died, both in the form of property and property rights, to families who are declared as heirs by law. However, in practice in the community of Dusun Pengkolan Village, there are still many who have not applied Islamic inheritance law. The purpose of this study is to determine the view of Islamic law on the practice of dividing the inheritance when the heir is still alive. Data sources were obtained from the Al-Qur'an, Hadith, KHI, and journals related to the research problem as well as interviews conducted in Pengkolan Hamlet Village. The results of the study concluded that the practice of dividing inheritance in some communities in Pengkolan Hamlet Village was not in accordance with Islamic law because the community distributed the inheritance when the heir was still alive. According to the view of Islamic law, the distribution of inheritance that occurs in the Pengkolan Hamlet Village community is not the distribution of inheritance property, but in practice it is more directed to grants, because the distribution of property is given when the muwaris has not died. Keywords : Inheritance, Heirs, Islamic Law